The influence of start-up entrepreneurship and disruptive business model on firm performance - Napatsaporn Niyawanont (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: This research aims to develop the constructs and to study the causal relationship between start-up entrepreneurship (SUE), disruptive business models (DBM), and firm performance (FPF) of start-ups in Thailand. Research Design & Methods: A quantitative research, a total of 186 samples from start-ups in Thailand. Data were collected by using online questionnaires with an entrepreneur/start-up founder/co-founder per company. The data were analysed through structural equation modelling. Findings: The new dimensions of SUE, DBM, and FPF reach a decent level of structural credibility and are suitable for measurement. SUE and DBM had a positive influence on FPF, while SUE had a positive influence on DBM as well. Implications & Recommendations: The results could be used to advance the potential of start-up entrepreneurs, strengthen the existing business model, or decide to develop a new business model that could develop brand new products/services in the markets to meet customer needs that change with technology advancements. Contribution & Value Added: The dimensions of the newly developed SUE, DBM, and FPF could be developed dynamically. These new dimensions have contributed to SUE acting as a mechanism of DBM development. The finding show that the new dimensions could be used to develop start-ups; to begin with, the new business model generation, technology-driven products/services development to meet the customer needs and seeking investors network. Thus, the impact of DBM will be strengthened, and the impact of FPF can gain a competitive advantage and improve profitability, as start-ups introduce a new business model with technological innovation that will redefine industries and restructure the economy.
Keywords: L26; M13; 330; startup entrepreneurship; disruptive business model; firm performance; structural equation modelling